Cold Water Swimming and Pregnancy: A Scoping Review and Consensus Recommendations - J Shawe; M Felton; JC Harper; C Mark Harper; R Stidson; M Tipton; S Blowers; K Fraser; S Hingley; E McGrath; G Bainbridge; Massey Heather (Lifestyle Medicine)
ABSTRACT Introduction Cold water swimming has increased in popularity and women wish to swim throughout pregnancy. There is a lack of evidenced‐based guidance to make decisions about the safety of immersion in cold water during pregnancy. Methods Closed social media groups were asked for specific questions in relation to cold water swimming and pregnancy. This highlighted concerns including water temperature, risks to the mother and fetus, and water quality. To find evidence‐based answers, a series of meetings brought together clinicians and researchers with expertise in cold water physiology, exercise physiology, fertility, obstetrics, neonatology, midwifery, water epidemiology, public health and representatives from the Open Water Swimming Society and an Open Water swimming social enterprise. Results Published data were examined via a scoping review process and four studies and eight reports were identified. Recommendations were made with evidence graded (mostly grade 4 expert opinion). Conclusion Research gaps highlight the need for research to enable accurate advice to determine whether it is safe for pregnant women to swim outdoors in cold water.